2006
DOI: 10.1007/s00392-007-0461-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a three-week intensive cardiac out-patient rehabilitation program in motivated patients with low social status

Abstract: The improvement in mean maximal performance of 100.5+/-31.4 to 123.1+/-36.2 W (p<0.01) achieved during CR was further improved to 128.7+/-40.9 W (p < 0,01) after 24 months. Of the patients, 61.2% reported regular physical activity during the 24 months of the study. The lipid management achieved by CR was maintained over 24 month. At I 65%, at II 84.4% and at V 82.4% of the patients with coronary artery disease (CAD) were undergoing lipid lowering therapy. BMI increased from 26.8+/-3.0 to 27.6+/-3.6 kg/m2 (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
2
8
0
7
Order By: Relevance
“…In a RCT following 394 patients for a mean 4.1 years after CR, Lear et al 11 reported a 5.6% decline in peak METs, which was similar in patients randomised to CR maintenance or standard care. Bjarnason-Wehrens et al 34 reported a slight (4.6%) but significant increase in peak workload (Watts) 2 years after CR. A large proportion of patients (61%) in this study reported daily physical activity within the past year.…”
Section: Discussionmentioning
confidence: 95%
“…In a RCT following 394 patients for a mean 4.1 years after CR, Lear et al 11 reported a 5.6% decline in peak METs, which was similar in patients randomised to CR maintenance or standard care. Bjarnason-Wehrens et al 34 reported a slight (4.6%) but significant increase in peak workload (Watts) 2 years after CR. A large proportion of patients (61%) in this study reported daily physical activity within the past year.…”
Section: Discussionmentioning
confidence: 95%
“…It was not before 1992 when the first model of a German ambulatory CR center was established at the Sporthochschule Köln [10]. This was followed by a variety of additional ambulatory CR projects [11]- [13]. In the meantime, ambulatory CR in Germany is officially supported by law and included into clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…In Deutschland hat sich die ambulante kardiologische Rehabilitation in den letzten Jahren langsam, aber stetig zu einer von Kostenträgern, Ärzten und Patienten akzeptierten Alternative zur stationären Maßnahme entwickelt. An der Effektivität der ambulanten Rehabilitation besteht kein Zweifel mehr [3,4]. Die Frage der Zukunft ist vielmehr, welcher Patient für welches Setting geeignet ist, und aus Sicht der Deutschen Fachgesellschaften ist sie noch nicht beantwortet.…”
Section: Wann Ambulante Und Wann Stationäre Rehabilitation?unclassified